Developing Students' Social and Religious Attitudes Through Religious Extracurricular Activities - Chasanah, Maghfirotun (International Proceedings of Nusantara Raya, 2024)
This study aims to analyze the impact of religious extracurricular activities, specifically Hadroh and Tilawah, on developing students' social and religious attitudes at MIN 1 Banyumas. The research method used is qualitative with a descriptive approach. Data were collected through observation, interviews with teachers and students, as well as documentation. The results of the study show that Hadroh activities help students develop social attitudes, such as cooperation, tolerance, responsibility, and leadership. Students learn to work in teams and appreciate the roles of each group member. Meanwhile, Tilawah activities play an important role in enhancing students' religious attitudes, particularly in fostering love for the Al-Qur’an and discipline in performing worship. Students participating in Tilawah show improvements in their ability to read the Al-Qur’an, understanding of tajwid, and deeper spiritual awareness. Full support from the school and teachers plays a crucial role in the success of these two activities. However, challenges such as a lack of motivation among some students and time constraints need to be addressed with a more intensive approach. Overall, Hadroh and Tilawah activities significantly contribute to shaping students' religious and social character, while also supporting their spiritual and social development through direct and collaborative learning experiences.